Voltage depending load models: validation by voltage step test - Agüero, Jorge Luis (2006)
This paper presents applications of the Exponential Static Load model used to represent voltage depending loads. This model has been used to represent loads of different types: Industrial, Residential and of Petroleum Extraction Fields. These loads belong to “Sistema Interconectado Patagónico” (SIP), a small power system of 1200 MW of peak load situated in the South of Argentina. Models of several load types have been validated by tests. Tests were made by applying steps to the feeding load voltage. Load voltage sensitivity coefficients were obtained for the different load types tested. Load models validated by tests were used for SIP modal analyse.